Pengembangan Model Webquest Pada Mata Pelajaran Ips Di Sekolah Menengah Kejuruan - Wardani, Wardani (FKIP Universitas Lampung, 2017)
This research aimed to create the effective learning model that is able to increase the students’ achievement seen from the attainment of KKM. The result of this present study was in the form of instructional system or learning stages applied in lesson plan and it has been evaluated by materials expert, the specialist of learning model design, and limited test with the following results; (1) the product of webquest model was successfully developed and it was able to be implemented in learning Social Studies toward students on grade X in SMK Negeri 2 Bandar Lampung, (2) the use of Webquest model the interest could increase students’ achievement or in other words could able to enhance the amount of students who passed the KKM. Key Word : model webquest, pembelajaran IPSDOI: http://dx.doi.org/10.23960/jpp.v17.i2.201701